Dinasti Umayah Dan Abbasiyah Polemik Sistem Kepemimpinan Dan Keruntuhannya - Ahmad Fananie; Nanang Mulyana (AL-MUFASSIR, 2021)
The reign of the Umayyad and Abbasid caliphs had incised Islamic civilization in their time, the progress of Islamic civilization cannot be denied from the role of the caliph in the Umayyad and Bani Abbasid dynasties. Every government experiences its period of growth, triumph and downfall. This research will analyze the causes of the fall of the Umayyad and Abbasid dynasties, and how the system of appointing a caliph during the Umayyad and Abbasid era changed, and what the difference is with the appointment of the caliph during the Khulafaurosidin era, as well as what values, principles and criteria must be possessed by a leader. Islam which was exemplified by the Prophet Muhammad and Khulafaurosidin, as a role model for Islamic leaders after him. This study uses a qualitative approach by taking sources from a bibliography such as books, journals, and other libraries